Bilateral Peritoneal Flaps Reduce Incidence and Complications of Lymphoceles after Robotic Radical Prostatectomy with Pelvic Lymph Node Dissection—Results of the Prospective Randomized Multicenter Trial ProLy. Issue 2 (15th August 2022) - Gloger, Simon; Ubrig, Burkhard; Boy, Anselm; Leyh-Bannurah, Sami-Ramzi; Siemer, Stefan; Arndt, Madeleine; Stolzenburg, Jens-Uwe; Franz, Toni; Oelke, Matthias; Witt, Jörn H.
Abstract : Purpose: The purpose of this study was to investigate the effect of a surgically constructed bilateral peritoneal flap (PIF) as an adjunct to robot-assisted radical prostatectomy (RARP) and pelvic lymph node dissection (PLND) on the incidence of lymphoceles. Materials and Methods: A total of 530 men with localized prostate cancer underwent a RARP with bilateral extended standardized PLND in a prospective randomized controlled trial. In group A, a PIF was created by suturing the margins of the bladder peritoneum to the ipsilateral endopelvic fascia at 2 points on each side. In group B, no PIF was created. The patients were followed 30 and 90 days after the surgery to assess the incidence, extent and treatment of lymphoceles. Results: Lymphoceles occurred in 22% of group A patients and 33% of group B patients (p=0.008). Symptomatic lymphoceles were observed in 3.3% of group A patients and 8.1% of group B patients (p=0.027). Lymphoceles requiring intervention occurred significantly less frequently in group A patients (1.3%) than in group B patients (6.8%, p=0.002). The median lymphocele size was 4.3 cm in group A and 5.0 cm in group B (p=0.055). No statistically significant differences were observed in minor or major complications unrelated to lymphocele, blood loss, or surgical time between groups A and B. Conclusions: Bilateral PIFs in conjunction with RARP and PLND significantly reduce the total incidence of lymphoceles, the frequency of symptomatic lymphoceles and the rate of associated secondary interventions.